2010
DOI: 10.1016/j.jtcvs.2010.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Staged repair significantly reduces paraplegia rate after extensive thoracoabdominal aortic aneurysm repair

Abstract: A staged approach to extensive thoracoabdominal aortic aneurysm repair may reduce the incidence of spinal cord injury. This is of particular importance in designing strategies involving hybrid or entirely endovascular procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(87 citation statements)
references
References 26 publications
3
79
0
5
Order By: Relevance
“…7, 26 Additionally, it has been previously demonstrated that staged open procedures, first thoracic aneurysm repair followed by distal abdominal repair, was associated with a decreased rate of spinal cord injury from 17% to 0%. 27 Our results demonstrate that this outcome can be replicated using TEVAR. An additional benefit may come from temporary aneurysm sac perfusion associated with type 1b endoleaks partially perfusing the spinal cord until the open surgery.…”
Section: Discussionsupporting
confidence: 57%
“…7, 26 Additionally, it has been previously demonstrated that staged open procedures, first thoracic aneurysm repair followed by distal abdominal repair, was associated with a decreased rate of spinal cord injury from 17% to 0%. 27 Our results demonstrate that this outcome can be replicated using TEVAR. An additional benefit may come from temporary aneurysm sac perfusion associated with type 1b endoleaks partially perfusing the spinal cord until the open surgery.…”
Section: Discussionsupporting
confidence: 57%
“…This improved outcome was observed both in staged open procedures and staged hybrid procedures in an animal model (4, 5, 12). In these experimental studies, an interval of 7 days between procedures was sufficient to improve outcome dramatically: from 40–50% paraplegia to 0%.…”
Section: Commentmentioning
confidence: 76%
“…Clinical observations of open surgical experience added to the credibility of this experiment: patients who underwent TAAA repair in two stages suffered paraplegia at much lower rates than patients with comparable operations done in a single stage (5). …”
Section: Introductionmentioning
confidence: 99%
“…Although replacement of the entire thoracoabdominal aorta during a single procedure still carries a significant risk of SCI, results from experimental studies as well as clinical experience at our institution suggest that paraplegia and paraparesis are almost never seen— even with an equivalently extensive total resection—if aneurysm repair is carried out in stages, with abdominal replacement following thoracic replacement (or vice versa) after an interval of weeks, months or years (12-14). Various existing reports identify patients undergoing endovascular TA aneurysm repair following previous or concomitant AA repair to be at higher risk for spinal cord injury (15-19).…”
Section: Discussionmentioning
confidence: 99%